Analysis of Factors Affecting User Satisfaction of E-Commerce M-CNI Application - Siagian, Ivan Tagor; Viany Utami Tjhin (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
CNI as an MLM Company needs to improve its competitiveness because the big challenges faced by the offline Direct Selling marketing system are starting to be abandoned with the choice of doing business in online media or Marketplace. Therefore, the Business Process of PT. CNI, because it no longer relies on the Network recruitment process but rather prioritizes a quality product marketing system run by CNI Business Partners, it is necessary to run an e-CRM Strategy by utilizing e-commerce application technology, namely M-CNI. The M-CNI Feature Component is an important part of the e-CRM Strategy in order to accelerate business processes that are more effective and efficient in conducting promotions, conveying information, building interactions to transaction activities. This study aims to reveal the analysis of feature factors in the M-CNI application on the satisfaction of its users through 3 aspects, namely Usability, Content Adequacy and Reliability. Through case study research at PT CNI, it is expected to make theoretical and methodological contributions in improving services to Business Partners as Users of the M-CNI application.